The 3rd submission of manpower and machinery & equipment for BRACU project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the 3rd submission of manpower and machinery & equipment for BRACU new campus project.